Chapter Dall'area di Broca al sensorio digitale, trasformazioni antropologiche in atto e 'cervelli in movimento': una mente incorporata in un mondo digitalizzato. - Morabito, Carmela (Moderna/Comparata, 2022)
The new forms of social communication, with the increasing presence of images within the text, make us necessary to reconsider the cerebral basis of literacy and theyr reconfiguration via neural recycling. In the theoretical framework of Embodied philosophy of mind, we propose an analysis of the 'extended writing", actually using emoticon and emoji, in the light of our contemporary neuropsychological knowledge (hemispheric specialization and the functional circuit of literacy).